Pengaruh Pengalaman, Otonomi, Dan Etika Profesi Terhadap Kinerja Auditor (Studi Empiris Pada Kantor Akuntan Publik di Wilayah Surakarta dan Semarang) - Kurniawan, Heru; , Dra. Nursiam, M.H., Ak., CA (2016)
Understanding the performance of the organization is the answer of the success or failure of organizational goals that have been applied. As a supporter of success in carrying out its duties and functions properly, it is necessary a good performance and quality auditor. This study aimed to analyze the return if the experience, autonomy, and professional ethics affect the performance of the auditor in public accounting firms in Surakarta and Semarang. From the study 6 public accounting firm in Surakarta and Semarang obtained the number of samples that can be processed as many as 52 respondents. The analysis tool used is multiple linear regression that includes test data quality (validity and reliability testing), classical assumption (normality test, multicollinearity, heteroscedasticity test), multiple linear regression, (coefficient determination R2, t test and test F). The results showed that the variables of experience, autonomy, and professional ethics affect the performance audit. This suggests that the experience, autonomy, and professional ethics affect the performance improvement auditor.